Improvement studies of Medicago sp. for the Mediterranean climatic conditions of Aegean region - Avcioglu R.; Geren H.; Munzur M. (The Genus Medicago in the Mediterranean region: Current situation and prospects in research, 1996)
Turkish research workers encounter many times different problems of agriculture in different regions of Turkey which has diversity of climatic conditions throughout the Anatolian peninsula. The coastal part of the Aegean region with an extreme Mediterranean climate is one of these agricultural regions and the shortage of hay and quality feed production is among the main obstacles existing in the animal husbandry sector of agriculture in the area. The main objective of the Pasture and Forage Crop Section of Field Crop Department, Agriculture Faculty, Aegean University is to develop research projects on the promotion of forage crop production and pasture management in this part of the country. Recent studies have been focused on the alfalfa improvement programs and on annual medics to be used for the marginal land renovations. Some basic results of alfalfa variety evaluation, single crop selection and annual medic comparison studies were discussed in this article.
Meeting of the Mediterranean Working Group on Medicago of the FAO/CIHEAM Inter-Regional Research and Development Network on Pastures and Fodder Crops, 1995/10/19-22, Hammamet (Tunisia)